Perspectives on Transitions in Refugee Education Ruptures, Passages, and Re-Orientations - Subasi Singh, Seyda; Jovanović Milanović, Olja; Proyer, Michelle (Verlag Barbara Budrich, 2023)
Refugees face transitions in their lives: at an individual, a social and a cultural level. This book covers various aspects of these transitions and their intersections with educational experiences. Studies from different country contexts show the complex relationships between individual, culture, society and institutions. Examining these relationships and experiences during transitional processes aims to contribute to a deeper understanding of the different types of transitions in the context of refugee education, which may lead to an improvement of support structures in the future.